Non-linear structural parameter identification using instantaneous power flow balance approach. Issue 5 (4th May 2021) - Anish, R.; Shankar, K.
ABSTRACT: In this paper, a non-linear parameter identification method for structures is presented, whereby the instantaneous power flow balance of the substructure of interest is enforced. The time-domain power flow into the non-linear substructure is balanced against the power transmitted to adjacent structures, damping and kinetic and strain energies. Enforcing this condition of matching the net power balance to zero, a numerical model is iteratively updated as an inverse problem. Here, the identification is carried out using a non-classical optimization search tool, particle swarm optimization algorithm. A cubic non-linearity in spring and a quadratic non-linearity in damper are modelled for non-linear parameter estimation using power flow concept and is a preliminary stage of non-linear joint parameter identification. Important numerical simulations are presented in this paper, which cover different load cases, measurement points and different combination of non-linearities under noise-free and noisy conditions. The identified results show significant improvements in non-linear identification accuracy compared to previous literature related to non-linear identification.